Ensino investigativo como recurso didático para promover autonomia e criticidade dos alunos de uma escola do norte de Minas - Eufrásia Patrícia Meira Mendes (2019)
Teachers of basic education are recurrently complaining of students that are uninterested, apathetic and without attitude. In order to minimize this current context, a didactic sequence was developed with the aim of stimulating students' critical thinking and autonomy using an investigative teaching, making them subjects in the teaching-learning process. The process basically consisted of encouraging students’ interaction in scientific activities, inspired by the project “UFMG e Escolas”, in a constructive and creative way. On this purpose, the dynamic "mystery" was carried out with the students, where the goal was to make them understand that, to conduct an investigation, it is necessary to start from a problem, raise information, propose hypotheses, and perform tests to reach a conclusion. In addition, it evidences the importance of ethics and teamwork in research. Secondly, the aim was to instigate students to identify some problems and, based on individual experiences and curiosity; create processes aimed at resolving them. Fourteen students conducted experiments in order to look for answers to problems using scientific characteristics. For the data collection, pre-and post-test questionnaires, testimonials, evaluative instruments, records and researcher’s observation were used. The qualitative data analysis was performed from daily observation based on teacher/researcher and students’ records, as well as the reports from other teachers of the students. The qualitative data were analyzed using the graphs generated by Google forms. The results of this study show that the investigative activities promoted students’ active participation in the construction of knowledge, providing a stimulating environment that promoted the skills of autonomy and critical thinking.